Diseases - Bunch, Bryan H; Tesar, Jenny E (Danbury, CT Grolier, 2006)
Alphabetically arranged articles presenting medical information on more than 500 diseases, discussing causes, symptoms, stages of the disease, its likelihood of striking, treatments, prevention, and long-term effects
v. 1. Abscess to blister -- v. 2. Blood to Crohn's disease -- v. 3. Cross eyed to fetus -- v. 4. Fever to hyperthermia -- v. 5. Immune system to multiple sclerosis -- v. 6. Mumps to polycythemia -- v. 7. Polymyositis to spasms -- v. 8. Spider bites to zoonoses
Includes bibliographical references and indexes
Hurg
5 8
Keywords: Diseases -- Encyclopedias -- Juvenile